PEMBERDAYAAN EKONOMI KELOMPOK UMKM JAYA BERSAMA DESA PANGKALAN JAMBI MELALUI PENGUATAN LITERASI DIGITAL - Hesti Asriwandari; Ashaluddin Jalil; Achmad Hidir; Syamsul Bahri; Yesi Yesi; Seger Sugiyanto (Jurnal Pengabdian Masyarakat Multidisiplin, 2025)
MSMEs face challenges in digital marketing that can hinder their economic growth. Therefore, this service activity aims to (1) Provide digital literacy about utilizing social media and product marketing marketplaces (2) Provide knowledge about wisely utilizing digital media. The method used is Participatory Rural Appraisal (PRA) with a socialization approach and direct assistance to MSME actors. The service was attended by around 25 people and has been carried out well and received positive feedback. The service team teaches how to market through digital media and strengthens the group so that they can play a role according to their respective fields. The service participants enthusiastically listened to the material explanation about digital literacy in the form of utilizing the marketplace platform for marketing their products. This kind of activity is still rarely obtained by the group so that they do not understand about business digitalization. The success factors in this service activity lie in teamwork, the need for information about digital literacy, and support for the implementation of activities from the parties. Meanwhile, the inhibiting factor lies in the limited time to monitor and see the final results of the input material provided. Nevertheless, the potential success of the activity to develop Jaya Bersama MSMEs is quite high. However, in the future, continuous support and assistance is needed to ensure that Jaya Bersama MSME players are able to carry out digital transformation adequately and independently.